Dūrinių kirčiavimo dėsningumai - Stundžia, Bonifacas; Mikulėnienė, Danguolė (Kalbotyra, 1989)
The following factors play an important role in the choice of accentuation models of nominal compounds of Standard Lithuanian: (1) morpho(no)logical (existence of the “strong” morphemes, namely, connecting vowel and the nom. sg. ending -ys, -ė; (2) semantic (the dependence of the compound upon a definite part of speech - noun or adjective, and also upon the type of bahuvrīhi or non-bahuvrīhi); (3) prosodic (shift of the accent to the right and the existence of “métatonie douce”).For most nouns and adjectives of the non-bahuvrīhi type stem juncture plays a significant role; the accent usually falls either on the connecting vowel or, if it is absent, on the syllable directly preceding the stem juncture. In both cases this, as a rule, is the antepenultimate syllable, the accentuation of which is connected with the shift of accent to the right in the first two-syllabic component (including the connecting vowel), the predominance of the acute, and partial disappearance of the accentual paradigms 34a and 34b in spoken Lithuanian.The majority of adjectives and nouns of the type of bahuvrīhi are characterized by an accent on the penultimate syllable with which “métatonie douce” and a shift of accent to the right in the second two-syllabic component is connected.